How to secure a high quality knowledge base in a rule-based system with uncertainty? - Jankowska, Beata M. (Zielona Góra: Uniwersytet Zielonogórski)
Although the first rule-based systems were created as early as thirty years ago, this methodology of expert systems designing still proves to be useful. It becomes especially important in medical applications, while treating evidence given in an electronic format. Constructing the knowledge base of a rule-based system and, especially, of a system with uncertainty is a difficult task because of the size of this base as well as its heterogeneous character.
Keywords: rule-based systems; uncertainty; knowledge base; truth maintenance module